Efforts to Improve Motivation To Learn To Pray by Applying The Demonstration Method To Students In The RA Alfithriyah V, Watuagung, Pasuruan, East Java - Widati; Widanarti; Widiarti, Wida; Afriyanti, Widhi (Jurnal Cendekia Islam Indonesia, 2025)
Motivation to learn to pray in early childhood is an important aspect in the formation of religious character from an early age. This study aims to analyze the effectiveness of the application of the demonstration method in increasing the motivation to learn to pray in students of the RA Al-Fithriyah V Watuagung group, Pasuruan, East Java. The research method used is classroom action research (CAR) with a qualitative and quantitative approach. The subjects of the study were students of the RA group who had difficulty in understanding the procedures for praying. Data were collected through observation, interviews, and questionnaires to measure changes in learning motivation. The results of the study indicate that the application of the demonstration method directly can increase students' understanding and interest in learning to pray. This method provides a more interactive learning experience, allowing students to directly imitate the movements and readings of prayer with teacher guidance. In addition, direct feedback from the teacher strengthens students' understanding. Thus, the demonstration method has proven effective in increasing the motivation to learn to pray in early childhood. The recommendation from this study is that the demonstration method be applied more often in Islamic religious learning in RA to build stronger prayer habits from an early age.